(untitled) (Agrária (São Paulo. Online), 2013)
The process of creating the mosaic of protected areas in Jacupiranga was unprecedented in the State of São Paulo which analysis leads us to important impacts on the conservation and rural communities involved. If we consider the characteristics of the old Jacupiranga State Park (Parque Estadual de Jacupiranga – PEJ), with the misconceptions of the overlap in areas with resident communities, the presence of more than 8,000 people in 40 rural districts in its perimeter; environmental conflicts and territorial disputes; lack of financial and human resources management, it appears that the creation of Mosaic was the best alternative for mediation of conflicts, developing strategies for conservation of the area and access to land. If, on one hand, the creation of the former Jacupiranga State Park followed the assumption of separation between society and nature, the creation of the mosaic has promoted a process of dialogue and contexts of community participation, enabling the construction of agreements and consensus for land use planning that allows for the conservation and rural development site. From Territory of fear to Territory of rights, labor and citizenship: this is the challenge that now lives Mosaic of Conservation and the Jacupiranga this paper analyzed using the methodology of fieldwork, contextualized description and participant observation.